#TITLE_ALTERNATIVE# - ALKAUTSAR (NIM:10206034); Pembimbing : Dr. Eng. Suprijadi, ADHITYA
The sighting sense of human eyes is still regarded as the best tool to detect and select information from various kinds of objects. Unfortunately, humans cannot always be in every environment or observing every physical phenomenon since the distance or danger factor are always present too. One of the solutions to this is by utilizing object tracking which is a direct application of digital image processing concepts. Nonetheless, object tracking can also be used to observe a closer phenomenon such as the harmonic motion of a spring. In this final project, the motion of a spring is observed by a self-developed object tracking system that utilizes digital image processing. There are two methods done, which are the static method and the dynamic method. In the static method, the physical parameter of displacement for varying masses is sought, meanwhile in the dynamic method the parameter obtained is the period for varying masses. By entering each parameter into HookeÃ‚Â’s law, the spring constant can be obtained by both methods. The spring constant difference value between the results of image processing and mechanical use for the static method is 2.51%, while for the dynamic method it is 4.05%.